Analisis Pengetahuan Ibu tentang Stunting terhadap Upaya Pencegahan Stunting di Posyandu - Ratna Feti Wulandari; Nirmala Kusumaningrum Sunaryo; Vide Bahtera Dinastiti (JURNAL KESEHATAN PRIMER, 2025)
Background: Stunting is a condition of impaired growth in children under five years of age (toddlers) due to chronic malnutrition and recurrent infections, particularly during the first 1,000 days of life. It is caused by multiple factors. Some of the primary causes of stunting include poor parenting practices, such as the mother's lack of knowledge about nutrition, limited access to health services, insufficient access to nutritious food, and inadequate access to clean water and sanitation. Objective: This study aims to analyze mothers' knowledge of stunting and its impact on stunting prevention efforts. Method: This research employed a correlational analytic design with a cross-sectional approach. The study sample consisted of mothers of toddlers from Posyandu Kenanga 5, with a population of 55. Purposive sampling was used to select 40 respondents. A questionnaire was utilized as the instrument for data collection. The Chi-square statistical test was applied to analyze the data. Results: The findings of this study indicate that 53% of the mothers had sufficient knowledge about stunting. In terms of stunting prevention efforts, 50% of the respondents were categorized as having sufficient efforts. The Chi-square statistical test revealed a significant relationship between mothers' knowledge of stunting and their efforts to prevent it, with a p-value of 0.000.